The ABCs of Trait Anger, Psychological Distress, and Disease Severity in HIV. Issue 3 (11th November 2014) - McIntosh, Roger C.; Hurwitz, Barry E.; Antoni, Michael; Gonzalez, Alex; Seay, Julia; Schneiderman, Neil
Abstract: Background: Trait anger consists of affective, behavioral, and cognitive (ABC) dimensions and may increase vulnerability for interpersonal conflict, diminished social support, and greater psychological distress. The concurrent influence of anger and psychosocial dysfunction on Human Immunodeficiency Virus (HIV) disease severity is unknown. Purpose: The purpose of this study was to examine plausible psychosocial avenues (e.g., coping, social support, psychological distress), whereby trait anger may indirectly influence HIV disease status. Methods: Three hundred seventy-seven HIV seropositive adults, aged 18–55 years (58 % AIDS-defined), completed a battery of psychosocial surveys and provided a fasting blood sample for HIV-1 viral load and T lymphocyte count assay. Results: A second-order factor model confirmed higher levels of the multidimensional anger trait, which was directly associated with elevated psychological distress and avoidant coping ( p < .001) and indirectly associated with greater HIV disease severity ( p < .01) (comparative fit index (CFI) = 0.90, root-mean-square error of approximation (RMSEA) = 0.06, standardized root-mean-square residual (SRMR) = 0.06). Conclusion: The model supports a role for the ABC components of anger, which may negatively influence immune function through various psychosocial mechanisms; however, longitudinal study is needed to elucidate these effects.